Electrochemically self-doped WO3/TiO2 nanotubes for photocatalytic degradation of volatile organic compounds - Wang, Xiaoguang; Sun, Minghui; Murugananthan, Muthu; Zhang, Yanrong; Zhang, Lizhi (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Tailoring of the quantity and distribution of OVs in WO3/TNTs matrix by a simple electrochemical step.•Enhancement of charge-transport and reduction of electron-hole recombination by the incorporation of surface OVs.•12 times higher photo-current density and an enhanced photocatalytic removal efficiency of VOCs by self-doped R-WO3/TNTs.•Excellent durability during the photodegradation process by the R-WO3/TNTs with open channel structure of the TiO2 nanotubes. In this study, an electrochemically self-doped WO3/TiO2 nanotubes (R-WO3/TNTs) composite film was developed for the photocatalytic degradation of waste gas. The doping of oxygen vacancies (OVs) into the heterojunction of WO3/TNTs was conducted by a simple electrochemical approach, by which the quantity and distribution of OVs on surface as well as bulk were tailored with respect to the applied cathodic potential and the duration of the treatment. With an increase of applied cathodic potential as well as the duration, the quantity of OVs on WO3/TNTs was observed to be consistently raised, while those presented in the surface were raised initially and further showed a plateau trend as the duration extended at a fixed potential. The incorporation of OVs into WO3/TNTs enhanced the charge-transport resistance and reduced the electron-hole recombination, thereby showed an enhanced photocatalytic performance. The R-WO3/TNTs prepared by the electrochemical polarization process at −1.4 V (vs SCE) exhibited a 12 times higher photo-current density and obviously, an enhanced efficiency in the photocatalytic degradation of VOCs with a prolonging photostability compared to that of the pristine WO3/TNTs, under a simulated solar light irradiation. The single-time purification trial demonstrated the effectiveness of the R-WO3/TNTs composite in treating the VOCs for the practical application.